2012
DOI: 10.1186/1687-9856-2012-23
|View full text |Cite
|
Sign up to set email alerts
|

A single sample GnRHa stimulation test in the diagnosis of precocious puberty

Abstract: ContextGonadotropin-releasing hormone (GnRH) has been the standard test for diagnosing central precocious puberty. Because GnRH is no longer available, GnRH analogues (GnRHa) are now used. Random LH concentration, measured by the third-generation immunochemiluminometric assay, is a useful screening tool for central precocious puberty. However, GnRHa stimulation test should be considered, when a basal LH measurement is inconclusive. However optimal sampling times for luteinizing hormone (LH) have yet to be esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 9 publications
(13 reference statements)
0
32
0
Order By: Relevance
“…not been fully standardized and it is still debated which is the best procedure for such evaluation [13,14]. In this report, we performed a retrospective study to assess the usefulness of the Leuprolide ® stimulation test as a diagnostic method of idiopathic CPP in a group of girls who were evaluated for suspicion of CPP.…”
Section: The Usefulness Of the Leuprolide Stimulation Test As A Diagnmentioning
confidence: 99%
“…not been fully standardized and it is still debated which is the best procedure for such evaluation [13,14]. In this report, we performed a retrospective study to assess the usefulness of the Leuprolide ® stimulation test as a diagnostic method of idiopathic CPP in a group of girls who were evaluated for suspicion of CPP.…”
Section: The Usefulness Of the Leuprolide Stimulation Test As A Diagnmentioning
confidence: 99%
“…Alternatively, in those children needing it, GnRHa stimulation can be efficient, definitive and brief. While it has been reported that a single sample after GnRHa stimulation test at 1 hour is sufficient to identify CPP in 88 % gonadotropin measurement at 3 h post stimulation were 100 % predictive [7], we would agree that a 30 min sample is as good as later samples for those with CPP, even though the response among those without CPP continued to rise after this time [8 • ]. This report, plus another recent report finding that either a 20 or 40 min sample was reported to be sufficient [9], adds to the growing credibility of this more efficient diagnostic approach.…”
Section: Documentation Of Pubertal Lh Secretionmentioning
confidence: 61%
“…Therefore, GnRHas have been used instead. A multitude of different protocols have been suggested, ranging from single sample LH levels to abbreviated or prolonged algorithms involving serial LH testing (19,20). Regardless of which of these tests is used, a peak stimulated LH level of ~ 4-6 mIU/L [21] or an LH/ FSH ratio >0.66 is considered pubertal by many endocrinologists [22,23].…”
Section: Laboratory Evaluationmentioning
confidence: 99%